ON PALEOTECTONIC BELONGING OF THE SUVANYAK METAMORPHIC COMPLEX (SOUTHERN URALS) FROM THE U-Th-Pb DATING OF DETRITAL ZIRCON GRAINS - B. G. Golionko; N. B. Kuznetsov; A. V. Strashko; T. V. Romanyuk; A. S. Novikova; A. S. Dubensky; V. S. Sheshukov; K. G. Erofeeva (Геодинамика и тектонофизика)
U-Th-Pb isotope dating of grains of detrital zircon from quartzites of the Suvanyak metamorphic complex, which forms the Suvanyak tectonic unit that forms the western part of the Uraltau uplift, located in the east of the West Ural megazone in the Southern Urals. The results of isotope dating of grains of detrital zircon from quartzites of the southern part of the Suvanyak metamorphic complex (samples G18-1 and R14-396) show that numerous populations of Late Neoproterozoic–Early Cambrian detrital zircon grains suggest a Peri-Gondwanan origin of the primary sources of detrital material for the protolith of the studied rocks.The structure of the Suvanyak tectonic unit involves metamorphic formations of different ages – Early Paleozoic in the south and Late Precambrian in the north, which are now formally united into a single Suvanyak metamorphic complex. Their differentiation requires additional research.For the Late Paleozoic southeastern margin of the Baltica (at that time already involved in the structure of the composite continent Arct-Laurussia), according to the results of isotope-geochronological study of detrital zircon from the sedimentary and metasedimentary sequences of the Southern Urals, a number of the following tectonic structures were identified. Near the southeastern edge of the margin, there was a Late Neoproterozoic–Early Cambrian oceanic basin, within which a volcanic arc or arcs were active during 650–520 Ma. The structure of the southeastern edge of the margin included the Peri-Gondwanan terrane or terranes (? Cadomian type), as well as thick Riphean-Early Paleozoic sedimentary sequences, autochthonous to the Baltica.